A social network approach to demonstrate the diffusion and change process of intervention from peer health advocates to the drug using community - Li, Jianghong; Weeks, M.; Borgatti, S.; Clair, S.; Dickson-Gomez, J. (2012)
Project RAP (Risk Avoidance Partnership) trained 112 active drug users to become peer health advocates (PHAs). Six months after baseline survey (N bl = 522), 91.6% of PHAs and 56.6% of community drug users adopted the RAP innovation of giving peer intervention, and 59.5% of all participants (N 6m = 367) were exposed to RAP innovation. Sociometric network analysis shows that adoption of and exposure to RAP innovation was associated with proximity to a PHA or a highly active interventionist (HAI), being directly linked to multiple PHAs/HAIs, and being located in a network sector where multiple PHAs/HAIs were clustered. RAP innovation has diffused into the Hartford drug-using community. © 2012 Informa Healthcare USA, Inc.